Influence of Tiktok Account @dokterdetektif Credibility on Followers Trust in Information - Hamzah, Adrian Fadhullah; Destiwati, Rita (Faculty of Law, Universitas Pekalongan, 2025)
The credibility of anonymous influencer accounts is a critical, yet unexplored factor in building audience trust in health information on social media, especially on platforms like TikTok. This study examines the influence of the credibility of the anonymous account @dokterdetektif (2.1 million followers) on the trust of its followers. Quantitative research was conducted through an online survey of 400 active followers (purposive sampling, Slovin formula, 5% margin of error). The 4-point Likert scale questionnaire measured three dimensions of credibility (attractiveness, expertise, trustworthiness) and two dimensions of trust (trusting belief, trusting intentions). Validity was tested using Pearson correlation, reliability using Cronbach's Alpha (α>0.7), and hypothesis testing using Spearman correlation and t-test. There was a significant correlation between account credibility and audience trust (r=0.576; p<0.05), with credibility explaining 43.4% of the variance in trust (R²=0.434). All three dimensions of credibility were rated